Testing the Prebisch-Singer Hypothesis since 1650 : Evidence from Panel Techniques that Allow for Multiple Breaks - Arezki, Rabah; Hadri, Kaddour; Loungani, Prakash; Rao, Yao. (Washington, D.C. : International Monetary Fund, 2013)
In this paper, we re-examine two important aspects of the dynamics of relative primary commodity prices, namely the secular trend and the short run volatility. To do so, we employ 25 series, some of them starting as far back as 1650 and powerful panel data stationarity tests that allow for endogenous multiple structural breaks. Results show that all the series are stationary after allowing for endogeneous multiple breaks. Test results on the Prebisch-Singer hypothesis, which states that relative commodity prices follow a downward secular trend, are mixed but with a majority of series showing negative trends. We also make a first attempt at identifying the potential drivers of the structural breaks. We end by investigating the dynamics of the volatility of the 25 relative primary commodity prices also allowing for endogenous multiple breaks. We describe the often time-varying volatility in commodity prices and show that it has increased in recent years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet